Screen printing : the ultimate studio guide from sketchbook to squeegee - Print Club London (London : Thames & Hudson Ltd, 2017)
Although the technique of screen printing dates back to first-century China, it became the preferred printing method of choice for musical and political counterculture movements of the 1960s, thanks to its ease, cost, and flexibility. It moved into the mainstream with Andy Warhol's iconic screen print of Marilyn Monroe, and was quickly adopted by artists such as Roy Lichtenstein and Robert Rauschenberg. Screen printing has become even more widespread with the many demonstrations, marches, and grassroots protests in the wake of the American presidential election of 2016. Screen Printing: The Ultimate Studio Guide is a definitive, fully illustrated manual on the techniques, materials, and processes of screen printing.
Equipment -- Materials -- Artworking your design -- The basic of printing on paper -- The basic of printing on T-shirts -- Artist spotlight -- Printing outside the box -- Making it -- How to put on a show.
Keywords: Screen process printing